2008
DOI: 10.1007/s00425-008-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of oil bodies in endosperm of oat grains

Abstract: Few microscopical studies have been made on lipid storage in oat grains, with variable results as to the extent of lipid accumulation in the starchy endosperm. Grains of medium- and high-lipid oat (Avena sativa L.) were studied at two developmental stages and at maturity, by light microscopy using different staining methods, and by scanning and transmission electron microscopy. Discrete oil bodies occurred in the aleurone layer, scutellum and embryo. In contrast, oil bodies in the starchy endosperm often had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…Besides their structural function in OBs, oleosins may serve as docking stations for other proteins at its surface and may participate in the biosynthesis and mobilization of plant oils (Parthibane et al, 2012a(Parthibane et al, , 2012b. Oleosins are probably involved in OB stability (Leprince et al, 1998;Shimada et al, 2008) and in the regulation of OB repulsion (Heneen et al, 2008), preventing the coalescence of OBs into a single organelle (Schmidt and Herman, 2008). Nevertheless, the precise functions of oleosins in OB biogenesis and dynamics have not yet been established.…”
mentioning
confidence: 99%
“…Besides their structural function in OBs, oleosins may serve as docking stations for other proteins at its surface and may participate in the biosynthesis and mobilization of plant oils (Parthibane et al, 2012a(Parthibane et al, , 2012b. Oleosins are probably involved in OB stability (Leprince et al, 1998;Shimada et al, 2008) and in the regulation of OB repulsion (Heneen et al, 2008), preventing the coalescence of OBs into a single organelle (Schmidt and Herman, 2008). Nevertheless, the precise functions of oleosins in OB biogenesis and dynamics have not yet been established.…”
mentioning
confidence: 99%
“…6 Sectioned sectors of grains at early and late developmental stages, 14 and 40 days after anthesis, were stained with Sudan Black B or Toluidine Blue O. 6 The low magnifications of whole sectors of the grain and higher magnifications of defined sites (Fig. 1) provide information on the distribution and appearance of lipids throughout the grain.…”
mentioning
confidence: 99%
“…Applying different microscopical approaches, it has been shown that oil bodies appear as distinct entities in the embryonic axis and the aleurone layer, and that they loose their integrity and fuse with each other into large masses in the rest of the endosperm during grain development. 6 The fusion of oil bodies in the starchy endosperm is probably correlated with the reduced amount of the protecting oil-body associated proteins (oleosins) documented in this tissue. 6 The aim of this report is to present microscopical data on the distribution of oil throughout the oat endosperm, not shown in Heneen et al 6 The structural observations were made on the highlipid oat cultivar Matilda with 10.3% lipids.…”
mentioning
confidence: 99%
See 2 more Smart Citations